Effects of familial and non-familial warmth during childhood and adolescence on sexual-orientation disparities in alcohol use trajectories and disorder during emerging adulthood. (1st December 2019) - Coulter, Robert W.S.; Jun, Hee-Jin; Truong, Nhan; Mair, Christina; Markovic, Nina; Friedman, M. Reuel; Silvestre, Anthony J.; Stall, Ron; Corliss, Heather L.
Highlights: We examined the associations of warmth on alcohol use trajectories and disorder. We investigated sexual-orientation differences in familial and nonfamilial warmth. Lower warmth was associated with alcohol use disorder but not alcohol use itself. Warmth mediated a small percent of alcohol use disorder for sexual minority women. Abstract: Background: We investigated sexual-orientation differences in typologies of self-reported familial and non-familial warmth in childhood (before age 11) and adolescence (ages 11–17); and tested whether warmth explained sexual minority emerging adults' (ages 18–25) heightened odds of having heavier alcohol use trajectories (AUTs) and heightened risk for past-year alcohol use disorder (AUD) compared to completely heterosexuals. Methods: Using self-reported data from the U.S.-based Growing Up Today Study cohort, latent class analyses identified typologies of familial and non-familial warmth during childhood and adolescence. Multivariable regression models tested our objectives. Results: Six warmth classes emerged, including: High-High (i.e., high familial and high non-familial warmth, respectively); High-Moderate; Moderate-Moderate; Moderate-Occasional; Occasional-Occasional; and Low-Low. Among women, sexual minorities had higher odds than completely heterosexuals of being in the Moderate-Moderate, Moderate-Occasional, and Occasional-Occasional versus the High-High warmth class. There were not significant associations between sexual orientation and warmth classes for men. Lower warmth classes were generally associated with greater past-year AUD, and mediated heightened disparities in AUD for sexual minority women versus completely heterosexual women (4.3% mediated), but not among men. Warmth classes were generally unassociated with AUTs, and did not mediate sexual-orientation differences in AUTs. Conclusions: Lower warmth was associated with greater alcohol-related problems, but not alcohol use itself. Warmth explained a small proportion of AUD disparities for sexual minority women—but not for men.